IMPLEMENTASI MEDIA BUKU CERITA BERGAMBAR BERBASIS KEARIFAN LOKAL (BURITA-BERBEKAL) UNTUK MENINGKATKAN MINAT BACA SISWA SEKOLAH DASAR - Neni Novitasari (Jurnal Pendidikan Dasar Borneo (Judikdas Borneo), 2024)
Reading interest refers to a person's enjoyment and attention towards the desire to read. Learning media are tools that can be used to enhance students' reading interest to achieve educational objectives. The Burita-Berbekal media can help students improve their reading interest. This study aims to determine the increase in students' reading interest after using Burita-Berbekal among fourth-grade elementary school students. The sample selection used simple random sampling. The data collection technique used questionnaires with instruments in the form of a list of questions/statements. The research design used a pretest-posttest control group design. The research results showed an average pretest score of 3.16, which falls into the fairly good category. Meanwhile, the posttest results showed an average score of 3.88, which falls into the good category. This indicates that there is an increase in students' reading interest after the implementation of Burita-Berbekal.